The role of computed tomography in the diagnosis of lung cancer - a case report - Cabaj, Justyna; Bargieł, Julia; Chmielewska, Izabela; Milanowski, Janusz (Journal of Education, Health and Sport, 2022)
Introduction Lung cancer has been the main oncological problem in the world for years. It is extremely important to use appropriate diagnostic methods that enable its detection and implementation of appropriate treatment. Aim The presented case shows the advantage of computed tomography over chest X-ray (X-ray) in visualizing neoplastic changes in the lungs. Case Study The paper presents a description of a patient diagnosed with centrally located advanced lung adenocarcinoma with a strong expression of PD-L1 qualified for treatment with pembrolizumab. Results and Discussion Presented case confirms that X-ray is less sensitive, especially in the case of centrally located tumors. Therefore, the emergence of a new cough in a smoker or ex-smoker should raise concerns related to lung cancer despite a normal X-ray image. The central location of the tumor may cause dramatic course of the symptoms. In the presented case, a sudden significant deterioration of the condition was observed due to atelectasis of the entire lung. Haemoptysis observed during hospitalization was another symptom of centraly located tumor mass. Conclusions In conclusion, the history of cigarette smoking, presence of typical symptoms should provide an in-depth diagnosis of lung cancer, despite normal X-ray. Diagnostic procedures include computed tomography in the first place. The course of centrally localized disease may change rapidly during on first cycle of treatment. Due to the possibility of serious complications of the ongoing neoplastic disease, the patient should be under constant medical supervision.